Brunei epidemiological stroke study: patterns of hypertension and stroke risk. Issue 7 (July 2016) - Lupat, Agong; Hengelbrock, Johannes; Luissin, Masliza; Fix, Mario; Bassa, Burc; Craemer, Eva Maria; Becher, Heiko; Meyding-Lamadé, Uta
Abstract : Objectives: Hypertension is the most important known risk factor for cardiovascular diseases. A cross-sectional study was conducted in Brunei Darussalam to estimate the prevalence of hypertension and its association with socioeconomic and life-style factors and impact on stroke incidence. Methods: Five thousand and sixty-three participants aged above 18 years from 2103 randomly selected households in the Brunei-Muara district of Brunei Darussalam were surveyed. Hypertension was defined as mean SBP at least 140 mmHg, DBP at least 90 mmHg, or taking antihypertensive medication and blood pressure was measured twice. Logistic regression models are used to analyze the association between hypertension/medication for hypertension and sex, age, overweight, education, smoking, family history of hypertension, and employment. Results: A total of 48.3% [95% confidence interval (CI): 46.9–49.7%] of all respondents were identified as hypertensive. Prevalence of hypertension was higher in men (52.8%; 95% CI: 50.7–54.9%) compared to women (45.0%; 95% CI: 43.2–46.8%) and women seek treatment more often than men. Age, overweight, lower levels of education, and a family history of high blood pressure are positively associated with the prevalence of hypertension. The prevalence of overweight (57.3%) and obesity (23.7%) is high and the attributable risk of hypertension for stroke is large. Conclusion: The prevalence of hypertension in Brunei is high in both women and men. Information campaigns and prevention programs are needed to be able to cope with the increasing problem of hypertension and resulting diseases like stroke in Brunei in the near future.